1991
DOI: 10.1002/jor.1100090214
|View full text |Cite
|
Sign up to set email alerts
|

Purified staphylococcal culture medium stimulates neutral metalloprotease secretion from human articular cartilage

Abstract: Human articular cartilage released significantly increased levels of metal-dependent enzymes capable of degrading collagen, casein, and gelatin at a neutral pH following exposure to a sterile, purified fraction of Staphylococcus aureus culture medium. Neutral metalloprotease activity was determined by radiolabeled substrate assays and substrate gel analysis. The enzymes were activated with 4-aminophenylmercuric acetate and were inhibited by 1,10-phenanthroline and ethylenediamine tetraacetic acid. Protein immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…MMP-2 and MV1P-3. as has been shown by Williams et al [34] and by us (data not shown), as well as proba bly other MMP-proteoglycanases. We chose a crude enzyme solution containing several MMP-proteoglycanases in order to determine whether Ro 31-4724 is a broad-spectrum in hibitor of MM P-protcoglvcanascs able to effi ciently block the PG loss mediated by several MMPs.…”
Section: Discussionsupporting
confidence: 72%
“…MMP-2 and MV1P-3. as has been shown by Williams et al [34] and by us (data not shown), as well as proba bly other MMP-proteoglycanases. We chose a crude enzyme solution containing several MMP-proteoglycanases in order to determine whether Ro 31-4724 is a broad-spectrum in hibitor of MM P-protcoglvcanascs able to effi ciently block the PG loss mediated by several MMPs.…”
Section: Discussionsupporting
confidence: 72%
“…It is possible that bacterial infection elicits a complex response that can not be manipulated by modification of a single pathway. Other bacterial toxins such as staphylococcal proteoglycanreleasing factor [25,26] and reactive oxygen species might also participate in the triggering of various cellular responses in bacteria-infected chondrocytes since both would be upregulated after infection and inhibition of their production could lessen the severity of arthritis [14,19]. However, it is important to emphasize that this study is a simplified in vitro model without consideration of extracellular matrix, synovial tissue, and other inflammatory cells.…”
Section: Extracellular Mutrix Protein Gene Modulutionmentioning
confidence: 99%
“…The bacteria itself can secrete a factor that accelerates the loss of proteoglycan from cartilage (Smith and Schurman 1986). The loss of proteoglycan is associated with increase in chondrocyte-derived neutral metalloproteinases (Williams et al 1991 ). Bacteria that have a collagen receptor can mediate adhesion and add to the virulence of the organism (Witalski et al 1993).…”
Section: Pathophysiology Including Morphology Biochemistry Geneticmentioning
confidence: 99%